2009
DOI: 10.1007/s00534-009-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Is pancreatectomy with arterial reconstruction a safe and useful procedure for locally advanced pancreatic cancer?

Abstract: Further discussion is required concerning surgical indications and significance. However, it is thought that resection is useful only when surgery of R0 has taken place for selected locally advanced pancreatic cancer (M0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 29 publications
1
58
0
1
Order By: Relevance
“…Eighteen patients with R0 resections had a one-year survival rate of 67 % and 13 months median survival, as opposed to R1/R2 patients who had a 6 month survival rate. The paper concluded that arterial resection is useful only when an R0 resection can be done in a patient with M0 disease [26]. Median operating time in this series was 686 min, and median blood loss was 2,830 mL, clearly illustrating that pancreatectomies with arterial resections are technically demanding cases.…”
Section: Oncologic Controversy: Pancreaticoduodenectomy and Arterial mentioning
confidence: 84%
See 1 more Smart Citation
“…Eighteen patients with R0 resections had a one-year survival rate of 67 % and 13 months median survival, as opposed to R1/R2 patients who had a 6 month survival rate. The paper concluded that arterial resection is useful only when an R0 resection can be done in a patient with M0 disease [26]. Median operating time in this series was 686 min, and median blood loss was 2,830 mL, clearly illustrating that pancreatectomies with arterial resections are technically demanding cases.…”
Section: Oncologic Controversy: Pancreaticoduodenectomy and Arterial mentioning
confidence: 84%
“…Amano and colleagues from Tokyo recently published their experience with arterial resections and pancreaticoduodenectomy [26]. In this series, 23 patients with pancreatic adenocarcinoma who underwent arterial resections with pancreatectomies were retrospectively reviewed.…”
Section: Oncologic Controversy: Pancreaticoduodenectomy and Arterial mentioning
confidence: 99%
“…The author believes that PVR should become a standard procedure during PD. Furthermore, there are many publications describing more aggressive types of resections in selected groups of patients including arterial resection, but are not considered routine and thus cannot yet be recommended (11,12,13).…”
Section: Scope Of Current Opinionsmentioning
confidence: 99%
“…Current oncological guidelines suggest that pancreatic tumours invading arterial structures render these cancers inoperable [10] . Nevertheless, attempts at resection involving reconstruction of the main arteries such as the coeliac axis, hepatic artery and superior mesenteric artery (SMA) have been reported, albeit in small case series [8,[11][12][13][14][15][16] . The study population for the meta-analysis is the largest in the published literature despite the unsurprising heterogeneity of the 26 studies that met inclusion criteria; a limitation acknowledged by the authors.…”
Section: Commentary On Hot Topicsmentioning
confidence: 99%